Satisfacción de los usuarios de la empresa Eléctrica CNEL - Los Ríos - Pérez Lazo, Angélica María (2021)
The investigation was developed within the framework of the (National Electricity Corporation), specifically in the Los Ríos CNEL EP Business Unit, which has seven agencies in the Province of Los Ríos, including its headquarters which is located in the Babahoyo city. The objective of this research was to determine the level of user satisfaction in relation to the service offered by this Business Unit. The methodology used is descriptive in nature, where techniques such as the survey were used, which was applied to 350 users using forms on the Google platform, and the interview that was applied to the leader of the customer service area. Among the main problems encountered and that generate dissatisfaction in users, are: High charges in consumption sheets due to inconsistencies in meter readings, Charging of additional values due to non-timely payment of schedules, impact due to voltage variation of the electric flow in the homes and public lighting in poor condition. It was also possible to detect that users have an acceptable perception of the organizational environment in the customer service area. The Los Ríos CNEL EP Business Unit to provide a quality service, considering that there is a Covid-19 Pandemic context, has contracted services from private companies to collect information from meters, cut off service and reconnect the service. Likewise, it has the service of Mixed Commercial Transport Companies, to attend to the problems in the different sectors.